Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kepuasan Kerja Karyawan PT. Empat Bersaudara Mandiri Sejahtera - Putri, Dhea Nihachi; Utomo, Fajar Cahyo; Setiorini, Amanda (PANDITA: Interdisciplinary Journal of Public Affairs, 2024)
The purpose of this research is to determine and analyze the magnitude of the influence of the work environment and compensation on the job satisfaction of PT employees. Empat Bersaudara Mandiri Sejahtera either partially or simultaneously due to the lack of employee job satisfaction that I got from the results of observations. This research uses quantitative methods, with a sample size of 83 respondents. The data collection technique used is primary data including questionnaires. The data analysis methods used is multiple linear regression, multiple correlation, and coefficient of determination. The results of this research indicate that the significance value for the influence of the work environment (X1) and compensation (X2) simultaneously on job satisfaction (Y) is 0.000 < 0.05 and the F value is 96.967 > 3.11 F table, so it can be concluded that H3 is accepted which means that there is a simultaneous influence of the work environment (X1) and compensation (X2) on job satisfaction (Y). However, there is still a dimension that is considered low received by employees, namely commissions which include commissions from sales results which are still considered unsatisfactory. PT employee job satisfaction. Empat Bersaudara Mandiri Sejahtera is considered good, meaning that employee job satisfaction is quite high